2019
DOI: 10.1002/micr.30458
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted microvascular anastomosis in head and neck free flap reconstruction: Preliminary experiences and results

Abstract: Background The da Vinci Surgical System has facilitated considerable advancements in surgery. The process and results of robot‐assisted microvascular anastomosis in real clinical situations have rarely been reported. This study presents our experience of performing robot‐assisted microvascular anastomosis in free flap reconstruction in patients with oropharyngeal cancer. Patients and methods This was a retrospective study of reconstructive operations using a free radial forearm flap for oropharyngeal defects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
(28 reference statements)
1
14
0
Order By: Relevance
“… 27 , 34 Lai et al (2019) noted equal outcomes for both RAS and non-RAS, but also reported that the RAS group used significantly smaller vessels for microanastomosis than non-RAS. 28 Similarly, another study demonstrated that RAS improved some lymphedema-related symptoms more than non-RAS following surgical intervention for breast cancer-related lymphedema. 30 …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“… 27 , 34 Lai et al (2019) noted equal outcomes for both RAS and non-RAS, but also reported that the RAS group used significantly smaller vessels for microanastomosis than non-RAS. 28 Similarly, another study demonstrated that RAS improved some lymphedema-related symptoms more than non-RAS following surgical intervention for breast cancer-related lymphedema. 30 …”
Section: Discussionmentioning
confidence: 95%
“…The average age among the study groups was 50.2 years old. Two studies were retrospective, 28 , 29 one was prospective, 30 and one was a case series. 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the COVID-19 pandemic, transoral robotic surgery was gaining widespread use among head and neck oncologic and reconstructive surgeons, 30 with outcomes comparable to those of nonrobotic anastomoses with use of a standard operating microscope. 31 This would allow spatial segregation of the operating surgeon from the high-risk field.…”
Section: Innovations In Microsurgerymentioning
confidence: 99%